Quantification of Catechins and Proanthocyanidins in Several Portuguese Grapevine Varieties and Red Wines - Sun,Baoshan (2001)
Catechins, oligomeric proanthocyanidins (degree of polymerization ranging from 2 to 12-15) and polymeric proanthocyanidins (degree of polymerization > 12-15) in several Portuguese grapevine varieties (Fernão Pires, Castelão, Vital, Vinhão, Espadeiro, Azal Tinto) harvested from the west and the north of Portugal in 1993 and 1994, and in some red wines from several Portuguese regions (Estremadura, Dão and Vinhos Verdes), were quantified using modified vanillin assay. In most grapevine varieties studied, the levels of catechins and proanthocyanidins in seeds in 1993 were roughly equal to those in 1994, although the climatological conditions were different between the two years. However, these values in skins of all tested varieties except Fernão Pires, obtained in 1994, were much smaller than those in 1993. Catechins and proanthocyanidins were located essentially in seeds, being 77,2% of total catechins of grape berry, 80,8% of total oligomeric proanthocyanidins of grape berry and 60,3% of total polymeric proanthocyanidins of grape berry, then in skins, being 19,7% of total catechins of grape berry, 19,0% of total oligomeric proanthocyanidins of grape berry and 38,9% of total polymeric proanthocyanidins of grape berry, and very little in pulp, being 3,1% of total catechins of grape berry, 0,2% of total oligomeric proanthocyanidins of grape berry and 0,8% of total polymeric proanthocyanidins of grape berry (mean values of two years). In seeds, the percentages of catechins, oligomeric and polymeric proanthocyanidins were respectively 4,2%, 29,4% and 66,4%; in skins, on the other hand, these values were respectively 1,8%, 13,0% and 85,2% (mean values of two years). The results also show the differences between the grapevine varieties from the west of Portugal and those from the north of Portugal. For all red wines analyzed, polymeric proanthocyanidins were predominant (averaging 65.5%), followed by oligomeric proanthocyanidins (averaging 27.9%), and catechins were presented in the lowest concentration (averaging 6.6%). Furthermore, the distribution of catechins, oligomeric and polymeric proanthocyanidins in red wines was similar to that in grapes.